2007
DOI: 10.7150/ijms.4.72
|View full text |Cite
|
Sign up to set email alerts
|

Role of Dietary Soy Protein in Obesity

Abstract: Soy protein is an important component of soybeans and provides an abundant source of dietary protein. Among the dietary proteins, soy protein is considered a complete protein in that it contains ample amounts of all the essential amino acids plus several other macronutrients with a nutritional value roughly equivalent to that of animal protein of high biological value. Soy protein is unique among the plant-based proteins because it is associated with isoflavones, a group of compounds with a variety of biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
185
1
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(204 citation statements)
references
References 92 publications
9
185
1
9
Order By: Relevance
“…28 The difference in the body weight was observed between the groups fed a HFD and normal diet, however, no substantial difference was detected in the daily food intake of animals. This observation revealed the fact that an increase in body weight was not dependent on the extent of food consumed by the rats but it was a result of consumption of HFD.As stated earlier high-fat diet resulted in lipid abnormalities associated to obesity include an raised serum concentration of fatty acids, TC, LDL-C, VLDL-C, TG and reduction in serum HDL-C. 29,30 results of the evaluation of lipid profile from control group of this study revealed similar observations thus here confirmed the establishment of the experimental model for the assessment of anti-obesity activity. This suggest that the fresh cow urine and its distillate may reduce pancreatic lipase activity thus reducing the absorption of dietary fat and regulates lipid profile.…”
Section: Discussionsupporting
confidence: 58%
“…28 The difference in the body weight was observed between the groups fed a HFD and normal diet, however, no substantial difference was detected in the daily food intake of animals. This observation revealed the fact that an increase in body weight was not dependent on the extent of food consumed by the rats but it was a result of consumption of HFD.As stated earlier high-fat diet resulted in lipid abnormalities associated to obesity include an raised serum concentration of fatty acids, TC, LDL-C, VLDL-C, TG and reduction in serum HDL-C. 29,30 results of the evaluation of lipid profile from control group of this study revealed similar observations thus here confirmed the establishment of the experimental model for the assessment of anti-obesity activity. This suggest that the fresh cow urine and its distillate may reduce pancreatic lipase activity thus reducing the absorption of dietary fat and regulates lipid profile.…”
Section: Discussionsupporting
confidence: 58%
“…The notable effects of the oil and hormone-like molecules of soybean have been studied in depth, but protein isolates for the treatment of obesity and related disorders only include the fatty acid metabolism [25], bone structure improvement [26], and steatosis models [27]. On the other hand, several studies have indicated that soybean protein consumption limits the body fat accumulation, improves insulin resistance and reduces plasma lipids [28]. Then, soybean is a good reference protein to compare with the effects produced by consumption of amaranth proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence is emerging that the type of dietary protein consumed can elicit different health effects and play an important role in disease aetiology (13) . In general, plant proteins have been related to health benefits more than animal proteins (14)(15)(16)(17) .…”
mentioning
confidence: 99%